Teaching Games For Understanding: Application of learning methods to volleyball material - Khaton Bagas Pambudi; Dian Pujianto; Yahya Eko Nopiyanto; Andika Prabowo (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
This study aims to determine whether using the TGFU learning method in playing volleyball can improve volleyball playing skills class X MIPA 3 students. In this study researchers used the Classroom Action Research (CAR) method. The subjects in this study were 36 students of class X MIPA 3 at SMA Negeri 1 Seluma. This research was conducted with pre cycle and in 2 cycles, where each cycle had 4 stages, namely: (1) planning, (2) implementation, (3) observation, (4) reflection. As for the results of the pre cycle percentage assessment was (46%), the results of observations of the teaching and learning process using the TGFU method in volleyball learning in the acquisition of the first cycle assessment percentage was (66%). Whereas in cycle II the percentage assessment was (85%), of students who had fulfilled the KKM value of 70. Based on the results of the research above, it can be concluded that using the TGFU method in volleyball learning can improve volleyball learning skills.